A study on the passive in selected english novels and their equivalents in vietnamese translational versions: a cognitive semantics perspective - Lê,Đình Thái Hà. (2016)
From Halliday‟s framework [9] the system of transitivity classifies the world of experiential meaning into different types of process, each of which has its own characteristics and can be differentiated from others by many features. This field of study originated from the fact that Material and Mental processes are distinguished from each other not only lexically but also grammatically. The way the study gives a description as well as a full analysis on distinguishing features in English and discusses applicable features in Vietnamese will present understanding of the systematic distinction between the two main processes. In a broader sense, the research serves as a path to get to know the relationship between grammar, meaning and context. The main theoretical bases of this thesis included Halliday‟s framework in Material processes and mental processes, transitivity system in Systemic Functional Grammar and Halliday and Hasan‟s view on processes. A combination of research methods was used for this thesis such as descriptive method, qualitative and quantitative method, and contrastive analysis method. As regards the data corpus, a total of 500 samples in English and Vietnamese were collected from the book in English “How to Win Friends and Influence People” by Dale Carnegie and in its Vietnamese version “Đắc Nhân Tâm” by Nguyễn Hiến Lê. The study revealed that between two types of clauses in the Transitivity system, material and mental clauses were used in both English and Vietnamese books.